Recurrent ischemia after percutaneous coronary intervention - M. P. Malgina; A. O. Nedoshivin; B. B. Bondarenko (Кардиоваскулярная терапия и профилактика)
Aim. To study the incidence, time of development, and the main causes of recurrent myocardial ischemia after effective revascularization and percutaneous coronary intervention (PCI). Material and methods. The study included 108 patients PCI with coronary artery (CA) stenting (85 men (78,7 %), 23 women (21,3 %)), who were followed for two years. All participants underwent clinical examination, blood biochemistry, electrocardiography (ECG), 24-hour ECG monitoring, stress echocardiography (EchoCG), and coronary angiography (CAG). Results. After PCI, favorable clinical course of coronary heart disease (CHD) was observed in 72 patients (66,7 %), while recurrent ischemia or a reduction in FC of effort angina was registered in 36 (33,3 %). Among women, recurrent or persistent ischemia was more prevalent than among men: 13 (56,5 %) vs. 23 (27 %) cases (p=0,015). Positive test stress EchoCG was observed in 30 patients. Based on the repeat CAG results, recurrent ischemia was due to incomplete myocardial revascularization (n=15), in-stent restenosis (n=12), or atherosclerosis progression (n=10). Conclusion. Active clinical examination is recommended to all patients after PCI, especially women. Stress EchoCG is recommended within first 9 months after PCI for angina-free patients and at any time for patients with recurrent angina.